FIRST BARITE FIND IN PRECAMBRIAN SEDIMENTARY DEPOSITS OF THE BALTIC SHIELD - Grinenko L.N.; Melezhik V.A.; Fetisova O.A. (My University, 1989)
Originally sedimentary sulfate-bearing rocks in the Precambrian of the Baltic shield were first identified in 1985. Sulfate sulfur was found in significant amounts only in chemogenic metacarbonate rocks and metamorphosed siliceous jasperoids, which also are relatively high in barium and sulfide sulfur. Sizable concentrations of both elements persist along the entire strike of the sulfate-bearing unit. When barium concentrations are above 2 weight percent, barite is visible in thin section. Barite-bearing carbonate rocks and jasperoid metamorphosed silicilytes form beds and lenses in crystalline dolomite and limestone bodies, ranging in thickness from 0.1 to 3 m. The origin of the barite is not clear.
Keywords: Precambrian; Precambrian; Докембрий